Optimalisasi Teknologi Informasi untuk Desa: Perancangan Aplikasi Penduduk dan Running Text LED - Ramli Ahmad; Dini Nur Hafizhoh; Abdul Rosid (Jurnal Teknologi Informasi untuk Masyarakat, 2026)
The advancement of information technology demands mastery of digital literacy, yet rural communities still face difficulties in accessing practical technology. This community service program aims to improve the technological skills of villagers through training on assembling and operating LED-based running text as a village information medium. A number of participants, consisting of village officials and general residents, were involved in this activity. The stages included preparation, socialization, hands-on training, evaluation, and follow-up. As a result, participants' understanding of the functions, components, and operation of running text increased by an average of more than 60%. On the other hand, the implementation of the Community Service Program was motivated by the village's need for more systematic and efficient population data management. The manual data collection process previously used made it difficult to search for data, update information, and compile administrative reports. This condition encouraged the design of a population data collection application as a solution. The focus of the activity was to design a backend system for centralized data management and storage. The methods used included observation, interviews, needs analysis, and system and database design. The design was tailored to the village's conditions to ensure optimal and sustainable implementation. The outcome is an application that enables population data to be managed more neatly, accurately, and accessibly. This system is expected to improve the work efficiency of village officials while minimizing data recording errors, as well as serving as an initial step in the implementation of information technology within the village environment.